KEANEKARAGAMAN JENIS BURUNG DIURNAL DI KAWASAN TAMAN WISATA ALAM BUKIT KELAM KECAMATAN KELAM PERMAI KABUPATEN SINTANG KALIMANTAN BARAT - Karmelitha, Yolanda; Dewantara, Iswan; Yani, Ahmad (Universitas Tanjungpura, 2021)
Birds are classified as wild animals that able to live in almost all types of habitat, they have high mobilities with an ability to adapt towards any types of wide habitat (Welty, 1982). Birds are wild animals with measured diversity levels. Birds can live in divers habitats, whether in forest habitats or not in forest habitats. TWA of Bukit Kelam is one of many habitats of birds. This research aimed to collect the data of diurnal birds' diversity types in TWA area of Bukit Kelam, this research is also expected to be able to give information related on what types of birds that live in TWA'sÂ area of Bukit Kelam to the citizens. This research used IPA (Index Point Abundance) method. According to the results of the research which have been done in TWA's area of Bukit Kelam, there are 11 families of 25 species of birds that live in the area. Diversity index of types (H) of all paths are 2,8029 which showsÂ that the diversity level in TWA's area of Bukit Kelam is classified as medium categorization. Diversity index of path 1 is 2,7248 types (H), diversity index of path 2 is 2,2230 (H), diversity index of path 3 is 2,116 (H), diversity index of path 4 is 2,1487 (H) and diversity index of path 5 is 1,7820 (H). Therefore, the diversity index value of diurnal birds' type in the TWA's area of Bukit Kelam with 1.121 Ha surface area is 2,80 (H) which means that the value of diurnal birds' type diversity index in TWA's area is categorized as medium.Keywords: Species Diversity, Diurnal Birds, Bukit Kelam Tourism Park.AbstrakBurung merupakan satwa liar yang memiliki kemampuan hidup hampir di semua tipe habitat, dan mempunyai mobilitas yang tinggi dengan kemampuan adaptasi terhadap berbagai tipe habitat yang luas (Welty, 1982). Burung merupakan satwa liar yang dapat diukur tingkat keanekaragamannya. Burung dapat menempati tipe habitat yang beranekaragam, baik habitat hutan maupun habitat bukan hutan. TWA Bukit Kelam merupakan salah satu habitat dari satwa burung. Penelitian ini bertujuan untuk memperoleh data keanekaragaman jenis burung diurnal pada kawasan TWA Bukit Kelam, penelitian ini juga diharapakan mampu memberikan informasi bagi masyrakat mengenai jenis burung apa saja yang terdapat di kawasan TWA Bukit Kelam. Penelitian ini menggunakan metode IPA (Index Point Abundance). Berdasarkan hasil penelitian keanekaragaman jenis burung yang dilakukan di kawasan TWA Bukit Kelam terdapat 11 famili dari 25 spesies burung yang mendiami kawasan tersebut. Indeks keanekargaman jenis ( ) pada seluruh jalur 2,8029 yang menandakan bahwa tingkat keanekargaman pada kawasan TWA Bukit kelam masuk dalam kategori sedang. Indeks keanekaragaman jalur 1 adalah 2,7248 jenis ( ), indeks keanekaragaman pada jalur 2 adalah 2,2230 ( ), indeks keanekargaman pada jalur 3 adalah 2,116 ( ), indeks keanekargaman pada jalur 4 adalah 2,1487 ( ) dan indeks keanekragaman pada jalur 5 adalah 1,7820. Jadi, nilai indeks keanekragaman jenis burung diurnal pada kawasan TWA Bukit Kelam dengan luas 1.121 Ha adalah 2,80 ( ) yang berarti nilai indeks keanekaragaman jenis burung diurnal pada kawasan TWA ini masuk dalam kategori sedang. Kata Kunci: Bukit Kelam, Burung Diurnal, Keanekaragaman.